Sosialisasi Reklamasi Tambang untuk Lingkungan Pertambangan Berkelanjutan di SMA N 19 Palembang - Restu Juniah; Rosihan Febrianto; Yuli Andriani; Syaifudin Zakir; Hisni Rahmi (Jurnal Pelayanan Masyarakat, 2025)
Mining is a two-edged sword, which makes a positive contribution to the economy but has a negative impact in the form of environmental degradation. Reclamation is a step taken in restoring former mining land to provide sustainable social, economic, and environmental benefits. This requires an early understanding of reclamation for the younger generation as agents of change. This community service activity aims to provide socialization about the concept, urgency, and practice of mine reclamation to students of Senior High School Number 19 Palembang as a form of environmental education towards sustainable mining. The methods used include interactive presentations and joint discussions. The results of the activity showed a significant increase in students' understanding of the issue of mine reclamation, as well as high enthusiasm and active participation in the entire series of activities. This activity contributes to fostering ecological awareness among students, as well as a form of collaboration between higher education institutions and schools in supporting sustainable development in the mining sector. The development of a collaborative-based follow-up program is needed so that this environmental education can take place continuously.